Modalidades de intervención de los psicólogos clínicos en Medellín, Colombia (2015)
ABSTRACT: This state of the art aimed to define the specific modalities of intervention clinical psychologists using two techniques: the rubric of content and a survey previously designed according to the categorical system defined for the project. In total 151 bibliographic records of national and international sources were reviewed and responded to the online survey 71 psychologists in Medellin residents who enroll their practice in the clinical field. The results in both data sources indicate a predominance of psychotherapy as a form of intervention, although the advisory, consulting and crisis intervention also highlights other options of clinical psychologists to meet the demands of care for people, differentiating each according to their objectives and their correspondence with the techniques and strategies expressed by authors and respondents. Finally rated modalities and its relationship to the levels of intervention known as health promotion, disease prevention and treatment is proposed.